How to bring immersive VR into the classroom: German vocational teachers’ perception of immersive VR technology - Spangenberger, Pia [Verfasser]; Matthes, Nadine [Verfasser]; Geiger, Sonja Maria [Verfasser]; Draeger, Iken [Verfasser]; Kybart, Markus [Verfasser]; Schmidt, Kristina [Verfasser]; Kruse, Linda [Verfasser]; Kapp, Felix [Verfasser] (My University, 2023)
„Affordances of immersive Virtual Reality (iVR) technology for learning (e.g., presence, immersion, interaction with 3D objects) and challenges of embedding this technology in teaching concepts are widely discussed. However, information on how German vocational teachers in the technical domain perceive iVR technology and if they intend to embed iVR in a classroom setting is still limited. Thus, the aim of the current study is to bring some insight into how these teachers perceive the value of iVR and to what extent their beliefs can be used as predictors for future intention to use. We conducted a study (n = 55) based on the Unified Theory of Acceptance and Use of Technology (UTAUT) containing items regarding performance expectancy, effort expectancy, social influence and facilitating conditions as determining factors as well as prior experience as a moderator for the intention to use. The main result we observed was that only performance expectancy significantly predicted the intention to use iVR in the classroom (β = 0.445, p = .001). In contrast to UTAUT, we also observed that prior experiences with VR headsets did not have an effect as a moderator variable, but it did have a direct effect on three of the determining factors of intention to use. Based on our results, we discuss implications for future embedding of immersive VR technology in classroom learning settings.“ (authors‘ abstract; BIBB-Doku)
Keywords: L 4.2 Mediengestützte Lehr-Lernformen; S 3.1.2.1 Berufliche Teilzeitschulen, Berufsschulen; P 3.2.3 Lehrer; 370; Virtuelle Realität; Digitale Medien; Medieneinsatz; Lernumgebung; Berufsschule; Berufsschullehrer; Befragung